THE INTERFERENCE MANIFESTATION THROUGH INTERLANGUAGE : A STUDY ON A MULTILINGUAL CHILD'S VERBAL PERFORMANCES - Heny E. Hartono; Tan Agung Haryono (Soegijapranata Catholic University, 2009)
Interference is often seen as an intrusion from the native language when a language learner is trying to perform the target language. In fact, it is more a part of the process of acquiring the target language which naturally happens before a language learner sucessfully achieves the target language proficiency. As a process rather than afinal product of learning language, it is hoped that it is not seen as a permanent incorrectness. The interference is manifested as an interlanguage. The interlanguage itself can be divided into 4 categories. namely overgeneralization, simplification, hypercorrection and avoidation. This research is trying to see the interference manisfestation of a multilingual child.